Predictive value of thrombus volume for recanalization in stent retriever thrombectomy. Issue 1 (December 2017) - Baek, Jang-Hyun; Yoo, Joonsang; Song, Dongbeom; Kim, Young; Nam, Hyo; Kim, Byung; Kim, Dong; Lee, Hye; Heo, Ji
Abstract This retrospective study investigated whether the volume or density of the thrombus is predictive of recanalization in stent retriever (SR) treatment. Consecutive patients treated with SR thrombectomy as the first endovascular modality were enrolled. The thrombus volume and density were measured on thin-section noncontrast computed tomography using 3-dimensional software. The patients were grouped by recanalization status and the number of SR passes. Among 165 patients, recanalization was achieved with the first pass in 68 (50.0%), 2–3 passes in 43 (31.6%), and ≥4 passes in 25 (18.4%) patients. The thrombus volume was smaller in patients with (107.5 mm3 ) than without (173.7 mm3, p = 0.025) recanalization, and tended to be larger with increasing number of passes (p for trend = 0.001). The thrombus volume was an independent predictor of first-pass recanalization (odds ratio 0.93 per 10 mm3, 95% confidence interval 0.89–0.97). However, the thrombus density was not associated with recanalization success. Recanalization within 3 passes was associated with a favorable outcome. In conclusion, the thrombus volume was significantly related to recanalization in SR thrombectomy. Measuring the thrombus volume was particularly predictive of first-pass recanalization, which was associated with a higher likelihood of a favorable outcome.